Cum putem citi însemnările neînsemnate - Cristina Ioana Dima (Revista de Istorie și Teorie Literară)
There was a custom in the 17th and 18th centuries for the readers of the old books to put down on the pages they were reading some notes about themselves or about the social, political and natural context they were living in. This article tries to demonstrate that these notes, aside from the cultural information they carry, represent a stage in the formation of the concept of “author”, as we understand it in our modern culture.